1986
DOI: 10.1080/0097840x.1986.9936771
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Recent Life Events Stress, Life Assets, and Temperament Pattern on Cardiovascular Risk Factors for Akron City Police Officers

Abstract: Police officers, as a group, experience many occupational demands with physiological and psychological effects that could be harmful to their health. A primary objective of this study was to analyze specific behavioral and physiological risk factors that could lead to hypertension and accelerated coronary artery disease. Three hundred thirty-one male Akron City police officers participated in the study. A group of volunteer males (n = 48) who worked in city clerical jobs were used as controls. Questionnaires w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…worries about the consequences of sleep loss). Addionally, studies have shown that shift workers had abnormally elevated norepinephrine levels, generally considered as a stress-marker and a risk factor for cardiovascular diseases (Ely & Mostardi, 1986;Park, Ha, Yi, & Kim, 2006;Yamauchi, 2004;Yamauchi, Iwamoto, & Harada, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…worries about the consequences of sleep loss). Addionally, studies have shown that shift workers had abnormally elevated norepinephrine levels, generally considered as a stress-marker and a risk factor for cardiovascular diseases (Ely & Mostardi, 1986;Park, Ha, Yi, & Kim, 2006;Yamauchi, 2004;Yamauchi, Iwamoto, & Harada, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…Ely and Mostardi [1986] found police officers to have greater resting norepinephrine levels, diastolic blood pressure, and life-change scores than male clerical workers, which could mean a greater degree of psychosocial stress. Other personal attributes may contribute, since the Type A behavior pattern, especially the components of hostility and internally directed anger, is associated with CHD [Manuck et al, 1986].…”
Section: Discussionmentioning
confidence: 95%
“…It is well known that police officers are a working population exposed to stress; as a group they experience many occupational demands with physiological and psychological effects that could be harmful to their health. According to Ely et al, increased psychosocial stress will increase blood pressure and this comes about through sympathetic activation, which increases norepinephrine levels 20) . Sources of stress for police officers may be the relationship with the public, exposure to episodes of criminality, rotating shift work and the need to maintain high levels of services in various contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the literature have studied the relationship between noise and hypertension and reported that the effects of noise on the cardiovascular system may be caused by autonomic nervous system activation with an increase in catecholamine release [15][16][17][18][19] . Besides these, human epidemiological studies have shown that the prevalence of hypertension is strongly dependent on psycho-social stressors [20][21][22][23] . It is well known that police officers are a working population exposed to stress; as a group they experience many occupational demands with physiological and psychological effects that could be harmful to their health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation